DETERMINANTS OF FINANCIAL DISTRESS: ANALYSIS OF DEBT TO EQUITY RATIO AND COMPANY SIZE IN THE BANKING SECTOR LISTED ON THE INDONESIA STOCK EXCHANGE IN 2020–2024 - Neng Mesa; Astari Dianty; Johannes Kristian Siregar (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2026)
This study is based on increasing pressure on Indonesian banking sector listed on the Indonesia Stock Exchange during 2020–2024. This study aims to examine the effect of Debt to Equity Ratio (DER) and firm size on distress in banking companies. The banking sector faced increased financial pressure during this period due to global economic slowdown and post pandemic recovery challenges which heightened financial risk exposure. Financial distress is measured using the Altman Z-Score. DER is calculated as total liabilities divided by equity, while firm size is measured by the natural logarithm of assets. This study uses a quantitative approach with secondary data from annual reports. Purposive sampling resulted in 31 banking companies, producing 155 firm observations. Data were analyzed using multiple linear regression. The results show that DER has a negative and significant effect on financial distress, while firm size has a positive and significant effect. Simultaneously, DER and firm size significantly affect financial distress. These findings indicate that higher leverage increases financial risk, while larger firms tend to have greater stability. This study provides implications for investors, regulators, and management in identifying early warning signals of distress. The findings contribute to risk assessment and support decision making to maintain banking sector stability and sustainable performance in Indonesia. This research enriches empirical literature by providing evidence from post pandemic conditions and offers insight for improving financial monitoring and institutional resilience within emerging capital markets.